2017
DOI: 10.1186/s12958-017-0286-x
|View full text |Cite
|
Sign up to set email alerts
|

NLRP7 contributes to in vitro decidualization of endometrial stromal cells

Abstract: BackgroundNucleotide-binding oligomerization domain (NACHT), leucine rich repeat (LRR) and pyrin domain (PYD) 7 containing protein, NLRP7, is a member of the NLR family which serves as innate immune sensors. Mutations and genetic variants of NLRP7 have been found in women with infertility associated conditions, such as recurrent hydatidiform mole, recurrent miscarriage, and preeclampsia. Decidualization of endometrial stromal cells is a hallmark of tissue remodeling to support embryo implantation and proper pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 50 publications
1
31
0
Order By: Relevance
“…HESCs maintained good viability over the course of the study, as indicated by live/dead staining, and no obvious differences were observed in viability for HESCs cultured in HESC growth medium or EGM (Supplemental Figure 1). Taken together, these results demonstrate that decidualization of endometrial stromal cells can be induced via hormonal stimulation in 3D cultures in a manner consistent with the established 2D decidualization assays [30][31][32][33][34].…”
Section: Presentation Of Hormonal Cues and The Decidual Response Of Esupporting
confidence: 81%
See 2 more Smart Citations
“…HESCs maintained good viability over the course of the study, as indicated by live/dead staining, and no obvious differences were observed in viability for HESCs cultured in HESC growth medium or EGM (Supplemental Figure 1). Taken together, these results demonstrate that decidualization of endometrial stromal cells can be induced via hormonal stimulation in 3D cultures in a manner consistent with the established 2D decidualization assays [30][31][32][33][34].…”
Section: Presentation Of Hormonal Cues and The Decidual Response Of Esupporting
confidence: 81%
“…We demonstrated that the GelMA hydrogel is capable of supporting endometrial stromal cell differentiation for at least 6 days in response to hormonal cues of 1 μM MPA and 0.5 mM 8-Br-cAMP. This decidualization protocol has been used extensively in literature primarily for 2D cultures [30][31][32]35], though some success has been reported inducing stromal differentiation with hormonal cues in 3D environments formed from thermally gelled collagen or crosslinked polyethylene glycol macromers [17,30,35,55,56]. In our study, stromal cells encapsulated in GelMA hydrogels maintained a decidual phenotype for 6 days in culture, as indicated by their epithelial-like morphology as well as increased secretion of characteristic decidual markers prolactin and IGFBP-1.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…A telomerase-immortalized HESC line was purchased from the American Type Culture Collection (ATCCR CRL-4003TM) and cultured according to the manufacturer’s instructions ( Krikun et al, 2004 ; Huang et al, 2017 ). Briefly, I-HESCs were cultured in phenol red-free Dulbecco’s modified Eagle’s medium/Ham’s F-12 (DMEM/F-12; Sigma-Aldrich Corp, United States) supplemented with 1.5 g/L sodium bicarbonate, 1% ITS + Premix (CORNING, NY, United States), 5 μg/μL puromycin (Invitrogen, Life Technologies, NY) and 10% charcoal-stripped FBS (HyClone, Logan, UT, United States).…”
Section: Methodsmentioning
confidence: 99%
“…NLRP7 is a member of NLRP subfamily and is especially known for the involvement of its mutated forms in recurrent hydatidiform moles ( 52 54 ). Several studies have also demonstrated a role for NLRP7 in different mechanisms related to pregnancy, including the in vitro decidualization of endometrial stromal cells ( 55 ), trophoblast lineage differentiation ( 56 ), and trophoblast proliferation, migration, and invasion ( 57 ). Khare et al ( 58 ) who demonstrated an ASC-dependent caspase-1 activation by NLRP7 in response to microbial acetylated lipopeptides, have first characterized the NLRP7 inflammasome.…”
Section: Introductionmentioning
confidence: 99%